Starsportswear Sdn. Bhd. / Muhammad Ridzwan Kamarul Baharaini... [et al.] - Kamarul Baharaini, Muhammad Rizwan; Mohd. Nasfi, Mohd. Nafis; Syed Abdullah, Syed Hussin; Ahmad Shuhaimi, Muhamad Shakirin; Zulkafli, Mohd. Syuhaib (2007)
Starsportswear Sdn. Bhd is a company sports clothing boutique. With multiple choise of some of the well known branded stuffis sold in our shio to satisfy our customer. This business operates in Souq al-Bukhary, Alor Setar, Kedah.